THE MEDIATION ROLE OF NON-PHYSICAL WORK ENVIRONMENT ON DEMOCRATIC LEADERSHIP STYLE ON TEACHER PERFORMANCE AT NURUL JIHAD EDUCATION FOUNDATION - Purwaningsih, Nining; Yani, Desi Gusti; Gunawan, Yanthi Meitry; Apriyanti, Metha Dwi (Univesitas Muhammadiyah Tangerang, 2024)
This research is quantitative using SPSS software version 22. The sample used was 50 respondents to teachers of the Nurul Jihad Education Foundation. Data collection uses primary data with questionnaire distribution. The data analysis technique used in this study is Path Analysis. The results of this study show that: (1) democratic leadership style has a positive and significant effect on teacher performance, (2) democratic leadership style has a positive and significant effect on the non-physical work environment, (3) the non-physical work environment has a positive and significant effect on teacher performance, (4) the non-physical work environment cannot mediate the influence of democratic leadership style on teacher performance because the direct influence value is 0.687 > from the influence of non-physical directly 0.265.